A Tuple Space for Social Networking on Mobile Phones - Sarigoel, Emre; Riva, Oriana; Alonso, Gustavo (Proceedings of the 26th IEEE International Conference on Data Engineering (ICDE 2010), 2010)
Social networking is increasingly becoming a popular means of communication for online users. The trend is also true for ofﬂine scenarios where people use their mobile phones to network with nearby buddies. In this paper, we propose a distributed tuple space for social networking on ad hoc networks. We describe the tuple space model and its operations and give evidence of its advantages for ad hoc social networking through several applications implemented on top of the tuple space.